The Influence of Account Receivable for Inventory of Income before Tax - Meilani Meilani; Pandoyo Pandoyo (Ilomata International Journal of Tax and Accounting, 2019)
This research aims to understand the influence of account receivable’s variable simultantly or partially and Inventory of Income before tax from Multi Sarana Persada Inc. in research period 2012-2015. The test was using Multiple Regression Analysis. The result shows that account receivable’s variable simultantly and inventory have an effect on income before tax. Account receivable’s variable has a significant effect on income before tax. However, the inventory’s variable does not affect income before tax.